(untitled) (Zaporizhzhia Historical Review, 2021)
In the article the historiography aspect of the problem ìSouth Ukraine in the context of the modern Ukrainian nation formation (the XIX ñ the beginning of the XX centuries)î is regarded. The stages of historiography process and the main trends of the problem studying are determined, the scientistsí achievements are described and research perspectives are outlined. It is emphasized, that Ukrainian historiography in the South Ukraine developed in the conditions of sharp struggle with the Russian official science, which didnít recognize the Ukrainian character of this region.